Preparation of silicon carbide foams using polymeric precursor solutions - Xujin Bao; Muhammad R. Nangrejo; Mohan J. Edirisinghe (2000)
A simple method was developed to produce silicon carbide foams using polysilane polymeric precursors. Polyurethane foams were immersed in polysilane precursor solutions to prepare pre-foams. Subsequently, these were heated in nitrogen at different temperatures in the range of 900±C to 1300±C. The silicon carbide foams produced in this manner showed well-defined open-cell structures and the struts in the foams were free of voids. The shrinkage which accompanies pyrolysis of the pre-foams was reduced by increasing the concentration of the polymeric precursor in the solutions.